Performance of Fast Absorbable Sutures and Histo‐Glue for Closing Incisions in Brown Trout. Issue 6 (24th August 2017) - Jepsen, Niels; Larsen, Martin H.; Aarestrup, Kim
Abstract: Telemetry has become a standard tool in fish research, but tagging methods still need refinement to achieve better results and to improve animal welfare. One of the problems reported from evaluations of surgical implants is unsatisfactory wound closure. Thus, researchers struggle to find better ways to close incisions, typically for tags implanted under field conditions. Problems are regularly encountered when closing incisions with traditional absorbable or nonabsorbable sutures, including decreased growth, slow wound healing, and erythema and necrosis at the suture site. We compared survival, growth, tag expulsion rate, and incision healing among three groups of dummy transmitter‐tagged wild Brown Trout Salmo trutta for which incisions were closed with two types of suture material (absorbable and fast absorbable) and histo‐glue. The tagged fish were kept in seminatural ponds for 20 d. Survival did not differ among groups, but growth of the tagged fish was lower than that of the control group. Histo‐glue gave the best healing but resulted in a high tag loss rate (33%). The fast absorbable sutures did not disappear faster than normal absorbable sutures, and healing and tag loss were similar. The use of fast absorbable sutures may hold potential for improving the procedure and should be further tested.